Naturalness of Asymptotically Safe Higgs - Pelaggi, Giulio M.; Sannino, Francesco; Strumia, Alessandro; Vigiani, Elena (Frontiers in Physics, 2017)
We extend the list of theories featuring a rigorous interacting ultraviolet fixed point by constructing the first theory featuring a Higgs-like scalar with gauge, Yukawa and quartic interactions. We show that the theory enters a perturbative asymptotically safe regime at energies above a physical scale $Λ$. We determine the salient properties of the theory and use it as a concrete example to test whether scalars masses unavoidably receive quantum correction of order $Λ$. Having at our dispose a calculable model allowing us to precisely relate the IR and UV of the theory we demonstrate that the scalars can be lighter than $Λ$. Although we do not have an answer to whether the Standard Model hypercharge coupling growth towards a Landau pole at around $Λ \sim 10^{40}\GeV$ can be tamed by non-perturbative asymptotic safety, our results indicate that such a possibility is worth exploring. In fact, if successful, it might also offer an explanation for the unbearable lightness of the Higgs.